Learning in a Foreign Country: Acculturative Stress in UUM’s International Students (S/O 14575) - Aziz, Azelin; Hassan, Hazlinda; Husin, Nurul Sharniza (UUM, 2021)
Students studying in a foreign country face disruption or loss of familiar support networks, which have been known to be effective coping techniques used in stressful situations. Loss of social support has been linked to various psychological consequences. This study investigated the effect of acculturative stress on academic satisfaction and well-being among Universiti Utara Malaysia (UUM) international students. The role of institutional support was examined in this study, that is, the university support moderation effect on these relations. The data were gathered by using questionnaires through various online mediums. A total of 119 responses were used in the analysis. By employing the SmartPLS software, four hypotheses were tested. From the findings, students from the African region reported the highest acculturative stress level, while students from the SEA region reported the lowest. Also, evidence of the direct effect of acculturative stress on students’ satisfaction and well-being was discovered, however, the moderation effects of university support on both relations were not substantiated. The implications and limitations of this study have also been discussed